(untitled) (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract : Media Visual Application of Learning on Wooden Construction to Improve Skills in Making Class XI Student Chairs at SMK Negeri 2 Panyabungan 2015/2016 Academic Year. This study aims to determine the application of visual learning media on basic competencies to apply the concept of connection and the relationship of wood to the type of construction and its size and students’ response to visual media. The achievement results in learning with classical KKM are M70. Where it can be seen that in the first cycle the average student learning outcomes were 66.87 with the number of students completing 8 people and those who did not complete the study were 8 people, in the second cycle the average student learning outcomes was 68.75 with the number students who complete increased to 11 people and those who did not complete the learning decreased to 3 people, in the third cycle the average student learning outcomes was 80 with the number of students completing increased to 15 people and those who did not complete learning decreased to 1 person. Keywords : Learning Outcomes, Skills in Making Seats, Visual Media. Abstrak : Penerapan Media Visual Pada Pembelajaran Konstruksi Kayu Untuk Meningkatkan Keterampilan Membuat Kursi Siswa Kelas XI di SMK Negeri 2 Panyabungan Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk mengetahui penerapan media pembelajaran visual pada kompetensi dasar menerapkan konsep sambungan dan hubungan kayu pada jenis konstruksi dan ukurannya dan respon siswa terhadap edia visual. Hasil pencapaian dalam pembelajaan dengan KKM klasikal sebesar â‰¥70. Dimana terlihat bahwa pada siklus I rata-rata hasil belajar siswa adalah sebesar 66.87 dengan jumlah siswa yang tuntas adalah 8 orang dan yang tidak tuntas dalam belajar adalah sebanyak 8 orang, pada siklus II rata-rata hasil belajar siswa adalah sebesar 68,75 dengan jumlah siswa yang tuntas meningkat menjadi 11 orang dan yang tidak tuntas dalam belajar menurun menjadi 3 orang, pada siklus III rata-rata hasil belajar siswa adalah sebesar 80 dengan jumlah siswa yang tuntas meningkat menjadi 15 orang dan yang tidak tuntas dalam belajar menurun menjadi 1 orang. Kata Kunci : Hasil Belajar, Keterampilan Membuat Kursi, Media Visual